Penerapan Contextual Teaching and Learning (CTL) pada Pembelajaran Tematik Kelas IV-B Madrasah Ibtidaiyah Negeri 6 Jember - Arfan Efendi; Abdul Muhith (HMPS PGMI FTIK IAIN Jember, 2020)
2013 curriculum is a must thematic learning applied in elementary, this is because the basic thematic learning is explained in Attachment to the Minister of Education Regulation No. 67 of 2013 concerning the Basic Framework and Curriculum Structure of Elementary Schools / Islamic Elementary School that for the learning process at the elementary levels from grade 1 to grade VI uses integrated thematic learning. Thematic learning in application needs to use appropriate methods in its application so that learning objectives can be accepted by students. Learning methods with Contextual Teaching and Learning become an appropriate alternative when paired with thematic learning. The focus of research in this thesis is How is the Implementation of Planning, Implementation and Evaluation of Contextual Teaching and Learning (CTL) in Thematic Learning Class IV-B Islamic Elementary School Negeri 6 Jember Academic Year 2019/2020 ?. This study aims to Explain the Implementation of Contextual Teaching and Learning (CTL) Planning, Implementation in Thematic Learning Class IV-B Islamic Elementary School 6 Jember Academic Year 2019/2020. This study uses a qualitative approach to the type of descriptive research. In determining the research subject using Purposive Sampling and using data collection techniques through observation, interviews and documentation. Kurikulum 2013 menjadi keharusan pembelajaran tematik diterapkan di SD/MI, hal ini dikarenakan dasar pembelajran tematik dijelaskan dalam Lampiran Permendikbud RI No. 67 Tahun 2013 tentang Kerangka Dasar dan Struktur Kurikulum Sekolah Dasar/ Madrasah Ibtidaiyah bahwa untuk proses pembelajaran pada jenjang SD/MI dari kelas 1 hingga kelas VI menggunakan pembelajaran tematik terpadu. Pembelajaran tematik dalam penerapan perlu menggunakan metode-metode yang tepat dalam penerapannya agar maksud pembelajaran dapat di terima oleh siswa. Metode pembelajaran dengan Contextual Teaching And Learning menjadi alternatif yang tepat bila di padukan dengan pembelajaran tematik. Fokus penelitian dalam skripsi ini adalah Bagaimana Penerapan Perencanaan, Pelaksanaan dan Evaluasi Contextual Teaching and Learning (CTL) pada Pembelajaran Tematik Kelas IV-B Madrasah Ibtidaiyah Negeri 6 Jember Tahun Pelajaran 2019/2020?. Penelitian ini bertujuan untuk Menjelaskan Penerapan Perencanaan, Pelaksanaan dan Evaluasi Contextual Teaching and Learning (CTL) pada Pembelajaran Tematik Kelas IV-B Madrasah Ibtidaiyah Negeri 6 Jember Tahun Pelajaran 2019/2020. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Dalam penentuan subjek penelitian menggunakan Purposive Sampling serta menggunakan teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Kata Kunci: contextual teaching and learning, tematik, madrasah ibtidaiyah